2022
DOI: 10.1021/acscatal.2c05358
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature CO Oxidative Coupling for Oxamide Production over Interfacial Au/ZnO Catalysts

Abstract: The conversion of carbon monoxide (CO) into high-value organic molecules has long been pursued by both industry and academia. One of the central challenges is to realize carbon−carbon coupling with high selectivity for CO insertion. We report here a highly selective Au/ ZnO composite catalyst for one-step oxidative coupling of CO with secondary amines, producing oxamides. The reaction is >99% selective under ambient conditions, which exhibits a subtle change of catalyst activity over ∼120 h in a fixed-bed reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Therefore, the coordination of Au at the interface with neighboring O, Zn, and other Au atoms in the cluster or NPs. [ 19 ] This depends on the surface behavior of defective ZnO and the concentration of Au 𝛿+ in photodeposition. The electrons are transferred from Au atom to oxygen vacancies sites to form Au‐O‐Zn linkages at the interface between the Au and ZnO.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the coordination of Au at the interface with neighboring O, Zn, and other Au atoms in the cluster or NPs. [ 19 ] This depends on the surface behavior of defective ZnO and the concentration of Au 𝛿+ in photodeposition. The electrons are transferred from Au atom to oxygen vacancies sites to form Au‐O‐Zn linkages at the interface between the Au and ZnO.…”
Section: Resultsmentioning
confidence: 99%
“…Overlayers can be used for advanced catalyst fabrication and application , during intense investigation of an SMSI. Particularly, overlayer formation creates a physicochemical partition between the metals, endowing NPs with excellent high-temperature sintering resistance. , In some situations, catalysts with an overlayer exhibit excellent catalytic activity, although the number of metal sites decreases due to encapsulation of the metal surface. Overlayer structures should be manipulated to understand an SMSI and fabricate high-performance catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…GJena et al revealed the effects of binding single hydrogen atoms in gold clusters through theoretical calculations [ 57 ]; this showed that introducing impurities such as H atoms in gold clusters can be highly efficient and cost-effective compared with using pristine gold clusters for CO oxidation. For example, He et al reported a highly selective Au/ZnO composite catalyst for the one-step oxidative coupling of CO with secondary amines, producing oxamides [ 58 ]. SiAu silicides were experimentally reported in early 1964 by Barrow et al [ 59 ].…”
Section: Introductionmentioning
confidence: 99%